Efektivitas Penggunaan Media Augmented Reality untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas VIII MTsN 1 Solok Selatan - Devitri, Madella; Anugrah, Septriyan; Eldarni, Eldarni; Kurniai, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Technological advances that can be used to increase knowledge are the development of information technology in the field of education. This study aims to determine the effectiveness of using Augmented Reality media to improve student learning outcomes in Natural Sciences teaching mates. Quantitative methods are used in the research. This study used a Quasi Experiment design, members of the experimental group as well as controls were not randomly selected. This study uses a nonequivalent control group design. This design is almost the same as the pretest posttest control group design. In this study, the sampling technique uses a purposive sampling technique. Based on the output of